ANALISIS KESULITAN GURU DI MASA NEW NORMAL PADA SDK ENDE 8 - Lely Suryani; Kristianus Jago Tute; Maria Purnama Nduru (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2022)
This research is motivated by the lack of optimal learning that takes place in schools due to the Covid 19 Pandemic. Learning involving teachers and students must be carried out not as usual because activities that gather many people must be avoided. Therefore, this study aims to analyze the difficulties of teachers in carrying out the learning process in the new normal due to covid 19. The type of research used is descriptive qualitative with data collection techniques in the form of interviews, observation, and documentation. The subjects in the study were 1 principal and 3 homeroom teachers for grade 1 and 3 students. The results showed that in order for learning to run optimally in the new normal with limited face-to-face, the principal and teachers made strategies with careful planning. This careful planning starts from preparing a Learning Implementation Plan that is in accordance with new normal conditions by condensing the material, namely conveying important points and giving assignments by emphasizing the completion of practice questions, and the teacher also conducts daily tests, mid-semester assessments. and end of semester assessment. Before the face-to-face meeting took place, the school also carried out procedures in accordance with the health protocol.